The Naqli and 'Aqli integration in the teachings of community health posting - Mohd Dzulkhairi M.R.; Zairina A.R.; Nooriah M.S.; Yunus M. (International Islamic University Malaysia, 2024)
The Community Health Posting teaching module is incorporated in the fourth year medical curriculum at Universiti Sains Islam Malaysia (USIM). The integration of Islamic principles and values in the medical curriculum is emphasized during the Community Health Posting. The Community Health curriculum allow students to appreciate and understand the medical and fiqh aspects of health and disease, the social issues in medical practice and research and to inculcate the practice of Islamic professional etiquettes. The teaching module illustrates the relevance of humanities in understanding illness and medical care within the community. Teaching and learning activities include components that enable the students to explore a wide range of influencing factors and how these affect the patients and their families. Issues pertaining to psychosocial and ecological perspectives of the community are also discussed. This posting utilizes various teaching and learning techniques such as lectures, tutorials, seminars, group discussions, educational visits, practical sessions and patient bedside teaching. In addition, the students are equipped with Islamic knowledge through the integration of Naqli and Aqli components in the Community Health Posting curriculum.